GEO-ECONOMIC ASPECTS OF TOURISM DEVELOPMENT IN THE MOUNTAIN REGIONS AND RESORTS IN BULGARIA - Petrov , Kamen; Stoyanova, Milena (Revista Inclusiones, 2020)
The growing importance and the role of spatial development of mountain regions as a commitment of the European Union for the implementation of a common regional policy on the continent as a whole, has put forward the need for a new approach and analysis of these areas. This analysis stems from the diversity and scale of the resource potential which the mountain regions have. The differentiation of the geo-urban development models of the mountain regions, which are a natural result of the impact of multiple factors, leads to the formation of a number of spatial features in the distribution of the population in the different in size mountain areas and types of mountain communities. This in a large extent sets out the possible aspects of tourism development in the semiurbanized territories outside the major ttourist spots. Defining the contemporary geo-urban realities in these areas through active research activities and objective analysis will make the formulation of clear objectives and priorities for a possible future policy for the development of the mountains.